The Undue Influence Doctrine and Its Function in Consumer Financing Cases - Azam, Syaiful; Mulhadi, Mulhadi; Harianto, Dedi (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The practice of freedom of contract in Indonesia is remain imbalance due to unequal position of the parties. This imbalance has been used by companies to take advantages and at the same time harm consumers. This study aims to explain the